The potential of biology-guided radiation therapy in thoracic cancer: A preliminary treatment planning study - Seyedin, Steven N.; Bassalow, Rostem; Mawlawi, Osama R.; Turner, Lehendrick M.; Patel, Roshal R.; Mazin, Samuel R.; Oderinde, Oluwaseyi M.; Voronenko, Yevgen; Wages, Cody A.; Olcott, Peter D.; Chang, Joe Y.; Balter, Peter A.; et al. (Frontiers in Oncology, 2022)
Purpose We investigated the feasibility of biology-guided radiotherapy (BgRT), a technique that utilizes real-time positron emission imaging to minimize tumor motion uncertainties, to spare nearby organs at risk. Methods Volumetric modulated arc therapy (VMAT), intensity-modulated proton (IMPT) therapy, and BgRT plans were created for a paratracheal node recurrence (case 1; 60 Gy in 10 fractions) and a primary peripheral left upper lobe adenocarcinoma (case 2; 50 Gy in four fractions). Results For case 1, BgRT produced lower bronchus V40 values compared to VMAT and IMPT. For case 2, total lung V20 was lower in the BgRT case compared to VMAT and IMPT. Conclusions BgRT has the potential to reduce the radiation dose to proximal critical structures but requires further detailed investigation.